Reasons for declining to participate in a trial of online cognitive behavioural therapy following orthopaedic trauma: A mixed methods study - Sheila Sprague; Jodi L. Gallant; Natalie Fleming; Sofia Bzovsky; Sarah MacRae; Mavis Lyons; Jose Manuel De Maria Prieto; Herman Johal; Paula McKay; Jason W. Busse (PLoS ONE, 2025)
The timely enrollment of study participants is critical to the success of clinical trials. Understanding factors that contribute to patients’ decision to participate in trials involving online cognitive behavioural therapy for pain management should prove helpful to optimize the design of study protocols. Fracture patients from an orthopaedic clinic who declined to participate in the Cognitive behavioural therapy to Optimize Post-operative rEcovery (COPE) trial were asked to complete a Research Participation Questionnaire that asked them about their previous experiences with clinical research and mental health therapy and their reasons for declining to participate in the COPE trial. At the end of the questionnaire, a subset of participants was offered the opportunity to participate in a telephone interview to further discuss why they declined to participate in the COPE trial. Sixty-four patients who declined to participate in the COPE trial completed the questionnaire and twenty of these participants agreed to take part in a telephone interview (31%). Twenty-two participants (34%) had previous experience with clinical research and six participants (9%) had received cognitive behavioural therapy (CBT) in the past. Excessive time commitment (41%) was the most commonly selected reason for not participating in the COPE trial, followed by a disinclination to participate in clinical research (19%). Four themes emerged from the interviews with participants: 1) belief that they could overcome mental health challenges after their fracture without external help; 2) belief that CBT might be helpful for some fracture patients, but not for themselves; 3) preference for online or in-person CBT; and 4) concerns regarding time commitment. To maximize enrollment, trials exploring the role of psychotherapy in recovery from orthopedic trauma should optimize time commitment of psychotherapy. Providing information in the patient consent process regarding evidence for psychotherapy and recovery from orthopedic trauma may also prove helpful in promoting patient enrollment.